Burn in Flames Post-Patriarchal Archive in Circulation - Browne, Sarah; Jones, Jesse (feminists@law, 2016)
This is the transcript of a presentation made by artists Sarah Browne and Jesse Jones at the Mixing Feminism, Legality and Knowledge seminar, held in June 2016 at the School of Law, Queen Mary Universtiy of London. The archive in circulation consists of objects involved in the regulation of the female body under the nation state and capitalism, which are labelled hazardous for future generations. It is one of a number of critical feminist tactics of resistance and defence, and exists for a future moment after the fall of patriarchy. The project forms part of a larger collaborative project by the artists called In the Shadow of the State.